Effectiveness and Efficiency of Budgeting in Governance - Isma Fadillah; Arif Zainudin; Agus Setio Widodo (Universitas Muhammadiyah Ponorogo, 2027)
This study aims to comprehensively analyze the implementation, impact, and supporting and inhibiting factors of budget efficiency in governance, focusing on Indonesia, Singapore, and Argentina. The approach used is a Systematic Literature Review of publications from 2020–2025, which are analyzed bibliometrically to map the dynamics of fiscal policy, budget management methods, and institutional structures that affect the efficiency of public resource allocation. The results of the study show that Indonesia implements efficiency through austerity policies and budget transfers to priority programs, Singapore emphasizes flexible results-based reallocation supported by comprehensive digitalization, while Argentina prioritizes radical fiscal reform through spending cuts and bureaucratic restructuring. These policies have proven capable of improving fiscal indicators and increasing fiscal space, but at the same time they create trade-offs in the form of the risk of economic slowdown and significant social burdens if they are not balanced with protection for vulnerable groups. Limitations in this study that need to be acknowledged by the academic community. Operational studies on the budget policy implementation process are limited by the use of secondary data. Future research should use a mixed-method approach or more measurable quantitative analysis. The database should be expanded to include non-Scopus sources such as Google Scholar, SSRN, and official government policy Keywords: Efficiency; Budgeting; Government; Governance;